Physical Activity and Transformational Leadership as Predictors of the Psychological Well-Being of Working Mothers [Aktivitas Fisik dan Kepemimpinan Transformasional Sebagai Prediktor Kesejahteraan Psikologis Ibu Bekerja] - Afiatin, Tina; Akhtar, Hanif; Reginasari, Annisa; Lutfikasari, Ervina; Penggalih, Bilhuda Ning; Nafiah, Naufi Ulumun; Sumawibawa, Nindya Dwi Apsari; Muslikhah, Nuri (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
The psychological well-being (PWB) of working mothers has an important influence both for family well-being and work performance. The increasing number of working women, and the existence of various changes in work, require a new explanation of the predictors of working mothers’ PWB. The purpose of this study was to examine the model of personal and interpersonal factors related to the PWB of working mothers, as mediated by work-family balance (WFB). The hypothesis of this study was a theoretical model stating the influence of physical activities and transformational leadership on PWB, through WFB, in accordance with empirical data. The subjects of the study were 536 working mothers of children, coming from Muslim communities and working under the directions of supervisors. The data collection used the Psychological Well-Being Scale, the Work-Family Balance Scale, the Physical Activities Scale, and the Scale of Perception of Transformational Leadership. The data analysis used the Structural Equation Model (SEM). The research results showed that physical activities and transformational leadership proved to have an effect upon the PWB of working mothers, through WFB. Kesejahteraan psikologis (psychological well-being - PWB) ibu bekerja berpengaruh penting, baik untuk kesehatan keluarga dan kinerja dalam pekerjaan. Peningkatan jumlah ibu bekerja, beserta dengan perubahan dalam pekerjaan, memerlukan penjelasan baru atas prediktor kesejahteraan psikologis ibu bekerja. Tujuan penelitian ini adalah untuk menguji model dari peran faktor personal dan interpersonal dalam kesejahteraan psikologis ibu bekerja, dimediasi oleh keseimbangan kerja-keluarga (work-family balance - WFB). Hipotesis penelitian ini adalah sebuah model teoretis yang menyatakan peran aktivitas fisik dan kepemimpinan transformasional mengenai kesejahteraan psikologis, melalui keseimbangan kerja-keluarga, berdasarkan data empiris. Subjek penelitian adalah 536 ibu bekerja yang sudah memiliki anak, dari komunitas Muslim, dan bekerja di bawah naungan supervisor. Pengumpulan data dengan menggunakan Skala Kesejahteraan Psikologis, Skala Keseimbangan Kerja-Keluarga, Skala Aktivitas Fisik, dan Skala Persepsi terhadap Kepemimpinan Transformasional. Data analisis menggunakan Model Persamaan Struktural (Structural Equation Model - SEM). Hasil penelitian membuktikan bahwa aktivitas fisik dan persepsi atas kepemimpinan transformasional berperan dalam kesejahteraan psikologis ibu bekerja, melalui keseimbangan kerja-keluarga. Received 7 November 2018; Accepted 27 July 2019; Published 25 October 2019.